(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article reveals the prerequisites for the emergence of shooting horting and reveals the problem of its classification in the system of martial arts and the prospects of its implementation as an element in the general education system, the preferences of the population involved in practicing this particular type of Ukrainian martial art. The relevance of the study lies in the systematization of knowledge about shooting horting and other types of martial arts with the aim of adopting experience, for the possible further use of this information in improving training systems and involving the population in this type of motor activity. The purpose of the work is to establish a place in the general classification of the martial arts of shooting horting and the prospects for the introduction of shooting horting as an element of physical culture of general education and motor activity. It has been established that shooting horting is a modern type of Ukrainian martial art. This is a new type of motor activity, which is at the same time a national sport, a modern Ukrainian martial art, an effective element of physical education and initial military training. As a system of physical education and sports, created on historical and ideological foundations, at the beginning of the 21st century. The classification scheme of martial arts is proposed and described, according to which shooting horting is a modern type of shooting martial art, which was created on the historical, cultural, ideological and philosophical foundations of the Ukrainian ethnos, using the latest tools and material and technical base, and is a modified form of shooting. It was found that with the help of shooting horting, as an element in general education, the following tasks can be solved: basic and special physical training, military-patriotic education of youth, initial military training, skills in safe handling of weapons, mastering the basic technical elements of shooting with several types of weapons , from various static positions and in motion, socialization, acquisition of quick and tactical thinking skills, psychological training of the population.